Adaptation, validity and reliability of the trait anxiety inventory - state for adults of the city of Trujillo - Bazán Izquierdo, Lili Claudina (2021)
The State-Trait Anxiety Inventory (IDARE) has demonstrated appropriate levels of validity and reliability for its use in different countries, however, evidence for its use in adults in the city of Trujillo has not yet been presented. The aim of the study was to adapt and validate the IDARE in a sample of adults. The sample consisted of 120 parents (96 women and 24 men) with a mean age of 35.18 years. The results indicated that the instrument presents validity guarantees based on the content and in the expert review, its items showed to be clear, coherent and relevant (VAiken> .70, p <.05). A second version of the IDARE, with 37 items (3 less in the trait anxiety dimension), reported better fit indices (x2 / gl = 1.74; RSMEA = .080 (95% CI = .072 - .088); SRMR =. 096; CFI = .988 and TLI = .987), with relevant items in the measure of each dimension (λ> .40) and acceptable reliability in both dimensions, state anxiety and trait anxiety (ω> .70). These results show that IDARE can be applied in the population studied with slight modifications from the original version.